The West’s diplomatic bungling on the land issue and how it triggered the land revolution in Zimbabwe: Paper presented at Midlands State University International Research Conference held at Zvishavane Campus, 29-30 September 2017 - Mudyanadzo, Wenceslaus (Midlands State University, 2017)
The paper argues that the failure of western diplomacy on Zimbabwe’s land issue was responsible for the breakdown of mutual trust which triggered the Land Revolution in 2000. Starting from the Anglo- American Proposals of 1977 to the Lancaster House diplomatic initiatives which revolved around the land issue, to the various proposals on the land issue by the Commonwealth, the European Union and the United Nations Development Programme in 1998 at the International Donors Conference on Land Reform and Resettlement, the West exhibited elements of dishonesty, intransigence, unreasonableness and reluctance to stick to the pledges made by the UK and the US governments at Lancaster House Conference to fund the land acquisition processes in Zimbabwe as a way of supporting the new political dispensation that emerged in 1980. The delays and frustrations that build-up as a results of western countries’ procrastination, the continuous change of goal posts and conditions for assistance convinced the Zimbabwe government and intended beneficiaries that the solution lay in their hands and not the West. A Zimbabwean solution was therefore adopted to solve a Zimbabwean problem through the land revolution.